María Casares: From Emigration to Exile - Hermida Mondelo, Sabela (Madrygal. Revista de Estudios Gallegos, 2015)
María Casares arises as an universal actress on her french exile, becoming a muse of Existentialism and a referent to her fellow republican countrymen and women. Thanks to her international artistic projection, she meets with the galician exiled in South America, thus becoming an icon, not only artistic, but political as well, for the banished Galician intelligentsia, hoping for the longed-for III Republic.